Bone regeneration after transcrestal sinus lift using nanoscale super-hydrophilic versus standard implant surfaces: a single-center, 12-month, parallel controlled clinical trial - Luigi Canullo; Domenico Baldi; Paolo Pesce; Vito Carlo Alberto Caponio; Alessio Triestino; Maria Menini (Oral and Maxillofacial Surgery, 2026)
Abstract Objectives Wettability of dental implants surface might be an additional key variable in the regeneration process and osseointegration. The aim of the study was to evaluate the effect of a new nanoscale roughness, combined with super-hydrophilic surface on bone volume change after trans-crestal sinus floor lift procedure for implant positioning. Materials and methods The study was reported according to SPIRIT guidelines. A 12-month, single-center, parallel group clinical trial was conducted to compare changes in bone regeneration and crestal bone level as shown on x-ray, following trans-crestal sinus floor lift using a collagenated hydroxyapatite graft and insertion of single dental implants with two different surfaces: moderately rough surface implants (Control Group – CG) and nanoscale super-hydrophilic surface implants (Test Group – TG). Radiographic bone volume and maximum height of regenerated bone as well as peri-implant crestal bone level were evaluated immediately following implant insertion and after 12 months. A multivariate regression model was built to address the impact of surface characteristics and clinical variables on the outcome. Results The study was completed by 25 participants (12 in the TG and 13 in the CG). CG achieved a volume change of 94.54mm 3 (SD 70.24), while the TG increased by 207.41mm 3 (SD 168.10) Focusing on bone height gain, CG presented 6.25 mm (SD 1.88), compared to 5.02 mm (SD 1.71) in the TG. For both outcomes, no statistically significant differences were found between the two groups ( p = 0.087 for bone volume change; p = 0.123 for bone height gain). Multivariate linear regression models only partially explained observed variance (respectively 8.6 and 35.4%), resulting in non-statistically significant predictions. Discussion Despite the trend of a higher bone volume observed in the hydrophilic surface group, taking into consideration all the variables, this study did not reveal any significant differences in terms of bone regeneration between groups. Conclusion Within the limitations of this study, implants with a nanoscale super-hydrophilic surface did not result in significantly greater bone regeneration than conventional moderately rough implants following transcrestal sinus floor elevation, although a trend toward increased bone volume was observed. Further clinical studies are required to clarify the potential regenerative advantages of hydrophilic implant surfaces.